PENGGUNAAN MEDIA SOSIAL YOUTUBE TERHADAP MOTIVASI BELAJAR SISWA PADA TEKNIK OTOMOTIF DI KELAS X TMO 1 SMKN BANTARKALONG - Kadarusman, Agus (Jurnal Inovasi dan Teknologi Pendidikan, 2022)
When studying automotive engineering, one of the sources you can use to visualize automotive engineering facts is YouTube. With YouTube, the teacher no longer has to explain or render information in her two-dimensional form. Emphasize only reflection on learning. Based on this, the formulation of the research question looks like this: How to use Youtube for automotive engineering teaching materials for light car engine maintenance? Using YouTube videos as a learning medium can be very helpful in your students' learning process. In short, it is very helpful for students to have additional information beyond library books, student manuals, and explanations from teachers. Availability of up-to-date information on various types of scientific and technological developments taking place in different parts of the world. So that the student's knowledge and insight expands and exceeds the planned goals. Then, while comparing with the information presented by the teacher, deepen your knowledge and look for things that need explanation or understanding. Learning to use YouTube videos as a learning medium has made it easier for students to learn and easier for teachers to teach. After attending a vehicle technology class, teachers often give video assignments. The pros and cons of using YouTube media for car learning is that it is easily accessible at any time and there is a lot of interesting learning videos and content that can help you better understand car learning